The Protective Effects of Vitamins C and E on The Oxidative Stress Induced by Sodium Metabisulfite on The Kidney Tissue in Adult Rats - Abdolnabi Peyravi; Zahra Firouzi; Mohammad Hassan Meshkibaf (Fasa University of Medical Sciences, 2016)
Background & Objective: Sodium metabisulfite which is used as a food preservative in the food industry, has adverse effects on body organs such as kidney and body grouth rate. In this research we have studied the protective effect of Vitamin C and E as antioxidants, on the kidney tissue damage after the consumption of Sodium metabisulfite. Materials & methods: Forty-eight Adult male Wistar rats of 150-200 grams were divided into 6 groups of 8 each. Rats in the experimental groups received Sodium metabisulfite (520 mg / kg body weight) by gavage feeding for 30 consecutive days. Also during this period, the experimental groups 2 and 3 received a daily dose of 100 mg / kg vitamins C and E, Respectively. The experimental group 4 received 50 mg / kg vitamin C plus 50 mg / kg of vitamin E by the same root. Control group received only normal diet and water. The placebo received vehicle (drug solvent) as well as normal diet and water. At the end of the exprimental period the body growth rate was measured between the groups. The histhopatological examination was performed on the kidney tissue sections. by light microscope Results: The results showed sodium metabisulfite in daily dietary could lead to the kidney tissue damage and reduced body weight in rats (p <0.05). However, vitamins C and E can reduce the kidney tissue damage and allow a normal growth weight (p <0.05). Conclusion: With this study we could conclude that the antioxidant effect of that vitamins C and E have a protective effect on renal damage induced by sodium metabisulfite consumption